PREDIKSI JARAK LUNCUR LONGSOR BERDASARKAN MEKANISME DAN PENYEBAB GERAKAN MASSA TANAH ATAU BATUAN - , MUHAMMAD QARINUR ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Landslide often occurs in tropical hills area such as Indonesia. Research on landslide hazard evaluation is necessary to decrease the impact in affected and surrounding areas. Empirical-statistical methods can be used to predict landslide runout distance in an effort to avoid the danger of landslide occurrences. This study aims to determine the relationship between landslide runout distance against high, slope, and volume based on mechanisms and causes of soil or rock mass movement. Data mainly from 106 landslides in Indonesia has been analyzed to search for possible correlations and empirical relationships, there are 34 rotational slides, 54 translational slides, 8 debris flows, and 10 rockfalls. Analysis begins by studying the characteristics of the data (explanatory data analysis) and then analyzed by using empirical methods such as geomorphological assessement and geometrical approaches. Then the data is processed by simple linear regression and multiple linear regression method using the R software. The results obtained from the analysis of the general empirical equation form of the relationship between height (H) and runout distance (L) is L=1,047 H1,09. This results indicate the higher altitude slopes, the greater distance will happens. The results of the analysis relationship between height and runout distance for the type of mass movements for rotational is L=1,346+1,788 H, translational is L = -3,88 + 1,578 H, debris flow is L = 0,682 H1,29, and rockfall is L = 2,223 H0,897. This result shows debris flows landslide runout distance greater than rotational, translational and rockfall. The results of the analysis relationship between height and runout distance of the trigger due to the rain is L = 1,267 H1,027, and by an earthquake is L = 0,574 H1,38. This results show the effect of runout distance caused by an earthquake larger than the effect due to the rain. The relationship between the runout distance and volume (V) obtained empirical equation is V=0,772 L2,108. This results indicate the greater runout distance occurs is affected by the growing volume of mass movement. The results of the analysis relationship between height and slope (Î¸) to runout distance is L = 1,448 H1,062 tan Î¸-0,482. This results indicate slope have a significant impact on the value of landslide runout distance.